Migrants and Economic Performance in the EU15: their allocations across countries, industries and job types and their (productivity) growth impacts at the sectoral and regional levels - Michael Landesmann; Robert Stehrer; Mario Liebensteiner (FIW - Research Centre International Economics, 2010)
Studies regarding the migrants' impact upon performance variables and in particular upon productivity growth - which is the focus of this study - are few although there has been an increased interest in this area. This study addresses this issue in a cross-country and regional perspective with a focus on EU-27 countries at the industry level. In the first part of the study the focus is on employment patterns of migrants regarding their shares in employment, the composition in terms of places of origin, and an important aspect of the analysis is the study of their skills' (measured by educational attainment levels) and the utilisation of these skills relative to those of domestic workers. The second part of the study conducts a wide range of descriptive econometric' exercises analysing the relationship between migrants employment across industries and regions and output and productivity growth. We do obtain robust results with respect to the positive impact of the presence of high-skilled migrants especially in high-education-intensive industries and also more generally - but less robustly - on the relationship between productivity growth and the shares of migrants and of high-skilled migrants in overall employment. There is also an analysis of the impact of different policy settings with respect to labour market access of migrants and to anti-discrimination measures. The latter have a significant positive impact on migrants' contribution to productivity growth. In the analysis of impacts of migrants on value added and labour productivity growth at the regional level we add migration variables to robust determinants of growth and find positive and significant relationships between migrants' shares (and specifically of high-skilled migrants) and regional productivity growth. The limitations of the study with respect to data issues, causality and selection effects are discussed which give scope for further research.
Keywords: F22; J61; O15; 330; migration; productivity; employment structures